Optimal operation of the coastal energy hub considering seawater desalination and compressed air energy storage system. (1st October 2021) - Jalili, Mehdi; Sedighizadeh, Mostafa; Sheikhi Fini, Alireza
Highlights: Modeling of optimal operation in an CCHP based CEH that includes a SPCASE and ISC, Using a RO-SWD to supply freshwater demanded by an MG, Modelling uncertainty of renewable generations and demands by scenario-based method, and. Reducing operation and environmental costs by 2.33% using SPCASE and ISC. Abstract: An optimal day-ahead operation of a microgrid based on coastal energy hub is presented in this paper. The proposed coastal energy hub includes generation units (wind turbine, photovoltaic cell, and combined cooling, heat and power), energy storage systems (ice storage conditioner, thermal energy storage system, and solar-powered compressed air energy storage), and seawater desalination with reverse osmosis technology as a flexible load. The purpose of the optimization is to minimize the operational and environmental costs subjected to numerous technical constraints. The suggested multi-objective problem considers the stochastic behavior of renewable generations as well as electrical, thermal, cooling, and freshwater demands under various scenarios. This paper uses an augmented epsilon constraint method for solving the proposed multi objective problem and implements a fuzzy based decision maker for choosing the suitable optimal solution amid Pareto front solutions. The proposed model implements the time of use program as a price-based demand response program. Implementation of the proposed framework on the typical coastal energy hub shows that using the solar-powered compressed air energy storage together with ice storage conditioner reduce the total operation cost (cost of purchasing electricity + cost of purchasing natural gas + cost of emissions) by 2.33% compared to the base case.